INTEGRATING EREADINGWORKSHEETS.COM FOR STRATEGIC READING IN EFL: TEACHERS’ PERCEPTIONS, CHALLENGES, AND MEDIATION - Buana, Randi; Sri Ardiasih, Lidwina; Bachtiar (ENGLISH, 2025)
Digital reading platforms have transformed the landscape of language instruction, particularly within the English as a Foreign Language (EFL) context, where traditional methods often fall short in meeting diverse learner needs. Grounded in sociocognitive and constructivist perspectives on digital literacy, this study explores how EreadingWorksheets.com enhances strategic reading comprehension and scaffolds metacognitive engagement in an Indonesian EFL program. Specifically, the research aims to investigate teachers’ perceptions of the platform’s effectiveness and the challenges and benefits experienced during its integration in the English Garden Course. Employing a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis involving twelve adolescent learners and their instructors. Thematic analysis revealed that teachers perceived the platform as effective for differentiated instruction and student motivation, while also observing improvements in learners’ strategy use. However, challenges related to cultural mismatches in content, limited digital access, and curriculum misalignment were also reported. These findings suggest that while EreadingWorksheets.com offers significant pedagogical affordances, its effectiveness depends on teacher mediation and contextual adaptation. The study underscores the critical role of educators in optimizing digital tools and provides practical insights for the design of technology-enhanced reading instruction that promotes cognitive depth and literacy equity in EFL classrooms.